PHYSICAL EXAMINATION ON STUDENTS ' PERCEPTION OF THE COURSE OF NURSING: FROM THEORY TO PRACTICE ASSISTANCE (Fiep Bulletin - online, 2016)
INTRODUCTION: the physical examination is regarded as a systematically organized survey of the patient in order to get physical changes and capacity or incapacity, distinguishing this way normal signs of abnormal (BARROS, et.al. .2010). OBJECTIVES: check the students ' perception of the course of nursing forward the importance of physical examination in healthcare practice. MATERIALS AND METHODS: For the development of the research was used field research, descriptive, exploratory qualitative approach. For the collection of data was used a structured interview containing 05 (five) issues, applied in June 2015. 34 students attended the 3rd, 4th and 5th grade of nursing degree from an educational institution in the city of Cascavel/PR. After the collection, the information was analyzed through the perspective of qualitative research methodological reference proposed by Bardin. RESULTS AND DISCUSSIONS: the research was divided into categories 02, thus described: category i: construction of knowledge of students of the course of theoretical and practical Nursing on physical exam, consisting of 03 (three) subcategories: i. the importance of physical examination in student perception, i. (II) theoretical knowledge of the physical examination, I.III ensino/aprendizado improvement contribution about the physical in practice and Category II : Students look forward to complexity of the physical exam, composed with 02 (two) sub-categories: II. (I) developing skills in front's education physical examination, II II the expectation and challenge difficulties faced by students in practice. CONCLUSION: it is evident the importance of physical examination for the students, however, there are still difficulties to be overcome with regard to pursuit of knowledge not only in the classroom and the technical skills to perform the same.
Keywords: physical examination; nursing; teaching